Estudos de propagação in vitro, caracterização e valorização de carqueja (Pterospartum tridentatum (L.) Willk) - Coelho, M.T. (2016)
The Pterospartum tridentatum (L.) Willk is widely used as medicinal plant for the treatment of digestive tract diseases and diabetes and for culinary purposes, however, characterization studies on this plant extracts are scarce. This work aimed to develop methodologies for micropropagation of this species and carry out characterization and application of the aqueous extracts. This study represents the first comparison analysis of extracts obtained from wild plants and aerial parts of plants in vitro multiplication. Micropropagation was very effective on large scale propagation with high multiplication rates. Aqueous extracts showed a good performance, high levels of phenolic compounds and antioxidant activity both in wild plants and in micropropagation. Phenolic profiles in in vitro shoots are very similar to extracts of wild plants during vegetative rest. The extracts revealed no antifungal activity, but nevertheless evidenced inhibition for some microorganisms. Within the monosaccharides, glucose is the predominant sugar in wild plants, since in the in vitro shoots uronic acids are the main components. An interesting result was the higher molar percentages of rhamnose and uronic acids detected on in vitro shoots compared to wild plants, which can make the in vitro plant material very useful to obtain these compounds. The application of chitosan bioactive coatings incorporating extracts has improved post-harvest storage capacity in cherry. The results allow propose these methodologies for obtaining extracts with bioactive properties from micropropagated material without depleting natural resources.